Enzymatic deinking of various types of waste paper: efficiency and characteristics - Chee Keong Lee; Darah Ibrahim; Ibrahim Che Omar (2013)
The aim of the present study was to characterize the enzymatic deinking of various types of waste paper. Studies on the optimization of enzymatic deinking have been performed previously using commercially available enzyme preparations containing cellulase and hemicellulase. The enzymatic deinking of different types of waste paper demonstrated a high efficiency of 86.6% on laser-printed paper, but a low deinking efficiency of 12.9% was obtained with newspaper. All enzymatic treatments significantly improved the drainage rate of the deinked waste paper. Enzymatic deinking increased the tensile index of magazine paper but reduced the tensile index of bubble jet-printed paper, photocopy paper and newspaper. Enzymatic hydrolysis caused a 21.1% reduction in the tear index for bubble jet-printed paper, but a 3.1% increase in the tear index was obtained for laser-printed paper relative to respective blank. In addition, enzymatic hydrolysis increased the burst index by 4.7% relative to blank for laser-printed paper. However, photocopy paper showed the highest reduction (8.3%) in the burst index relative to blank. Taken together, these results suggest that enzymatic hydrolysis is both advantageous and detrimental to the mechanical properties of deinked paper. Thus, the proper regulation of enzymatic hydrolysis is crucial to improve the quality of recycled paper.